ANALISIS NILAI LEVEL DAYA TERIMA MENGGUNAKAN PENDEKATAN MODEL PROPAGASI WALFISCH-IKEGAMI - ., Retno Niti Amalia (Faculty of Engineering, Universitas Tanjungpura, 2016)
ABSTRACT- Propagation model in cellular communication is needed to know the characteristic of propagation and it can be used to predict the value of receiving power level cellular network. The value of receiving power level is one of the indicator to see the signal quality and the influence in the prediction of beam coverage in BTS that is usually called coverage. Propagation model that would be used in this research was outdoor Walfisch-Ikegami. This research located at city center with taking the receiving power that radiated from BTS Santika that taken by using measurement from software G-NetTrack Lite in 3G Signal. The purpose of this research was to analyze the receiving power level by using Walfisch-Ikegami propagation model approach. The value of receiving power known by Walfisch-Ikegami propagation calculation and measurement by using G-NetTrack Lite towards 5 points street around BTS Santika was Agus Salim Street, Merapi Street, Antasari Street, Diponegoro Street, and Teuku Cik Ditiro Street. The result of propagation model calculation was founded as follow, -102.21 dBm, -89.68 dBm, -82.46 dBm, -96.05 dBm, and -76.49 dBm. The result of measurement by using the G-NetTrack Lite was founded as follow, -71 dBm, -73 dBm, -75 dBm, -81 dBm, and -75 dBm. The smaller the loss value or attenuation value, the value of receiving power that was founded would be closer with standard which has been set. The bigger the loss value or attenuation value, so the value of receiving power that was founded would be further with standard which has been set. Keywords: Received Power, Walfisch-Ikegami Propagation Model, Receive Signal Code Power.